21st-Century Competencies in Physics: Assessment Strategies for Critical Thinking, Problem-Solving, and Character Formation - Mor, Bhupendra; Patel, R N; Prajapati, Bharat (Schrödinger: Journal of Physics Education, 2025)
Purpose of the study: This study develops and validates an integrated, multimodal framework for assessing 21st-century competencies—critical thinking, creative problem-solving, and character formation—in secondary physics. It aims to provide an evidence-based alternative to conventional assessments that inadequately measure higher-order skills essential for real-world application. Methodology: A sequential mixed-methods design was employed with 320 secondary students and 15 teachers in Germany and Pakistan. The intervention used multimodal tasks (socio-scientific debates, engineering challenges) assessed with validated instruments, including the Watson-Glaser Critical Thinking Appraisal, Creative Problem-Solving rubrics, the Ethical Sensitivity Scale, and Augmented Reality simulations using GeoGebra. Main Findings: Multimodal assessments significantly outperformed traditional tests, with open-response tasks yielding a 48.8% gain in critical thinking. Creative Problem-Solving Stage 4 (Solution Planning) demonstrated a 133% skill gain and a strong correlation with student resilience (r=0.69). AR-based labs enhanced conceptual understanding by 25 percentage points over traditional labs. However, 78% of teachers reported inadequate training for implementation. Novelty/Originality of this study: This study presents a novel, cross-culturally validated framework that integrates socio-scientific issues, AR, and competency-based rubrics to assess cognitive, practical, and ethical skills in physics. It offers a scalable model to bridge the persistent gap between abstract physics knowledge and its real-world application, addressing documented assessment reform needs.